CLARISA (CGIAR Level Agricultural Results Interoperable System Architecture): a web-based service that collects and standardizes data from different platforms into aggregated information for the CGIAR system-level reporting - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
CLARISA: - gathered data from 11 CGIAR Research Programs and Platforms on key indicators; - contains more than 6,000 institutions from more than 160 countries organised in control lists; - hosted in 2021 and 2022 CGIAR Quality Assurance (QA) process; - provided the reference for standardised descriptors for CGIAR Innovations.